2022
DOI: 10.21037/tcr-21-1748
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of multiple bioinformatics studies to identify microRNA-target gene-transcription factor regulatory networks in retinoblastoma

Abstract: Background: In children, retinoblastoma (RB) is one of the most common primary malignant ocular tumors and has a poor prognosis and high mortality. To understand the molecular mechanisms of RB, we identified microRNAs (miRNAs), key genes and transcription factors (TFs) using bioinformatics analysis to build potential miRNA-gene-TF networks.Methods: We collected three gene expression profiles and one miRNA expression profile from the Gene Expression Omnibus (GEO) database. We used the limma R package to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Researchers have discussed the most important prognostic factors and potential mechanisms of RB through the use of existing data on RB and bioinformatics methods [ 8 , 9 ]. For example, an analysis conducted by Wen et al [ 10 ] identified two critical microRNA targets in RB: let-7a and let-7b by analyzing a variety of bioinformatics studies and identifying microRNA-target gene-transcription factor regulatory networks in RB. According to Gao et al [ 11 ] the long noncoding RNA (lncRNA) MEG3 may play a role in tumor suppression in RB, and the activation of Lnc00152 by Sp1 induces EMT through the miR-30d/SOX9/ZEB2 pathway and enhances the invasion and metastasis of RB cells through this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have discussed the most important prognostic factors and potential mechanisms of RB through the use of existing data on RB and bioinformatics methods [ 8 , 9 ]. For example, an analysis conducted by Wen et al [ 10 ] identified two critical microRNA targets in RB: let-7a and let-7b by analyzing a variety of bioinformatics studies and identifying microRNA-target gene-transcription factor regulatory networks in RB. According to Gao et al [ 11 ] the long noncoding RNA (lncRNA) MEG3 may play a role in tumor suppression in RB, and the activation of Lnc00152 by Sp1 induces EMT through the miR-30d/SOX9/ZEB2 pathway and enhances the invasion and metastasis of RB cells through this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 10 years, bioinformatic analyses, e.g., Encyclopedia of Genes and Genomes (KEGG) pathway, disease ontology semantic and enrichment (DOSE) and protein-protein interaction (PPI) analyses, etc., have been widely used in the investigation fields of genomics and proteomics, due to that they can comprehensively discover the biological mysteries of large and complex biological data accounting for physiological and pathological alternations of organism, or changes of organism in response to external stimuli ( Yu et al, 2015 ; Wen et al, 2022 ). For the bioinformatic analyses, differentially expressed miRNAs (differentially expressed genes (DEGs) or differentially expressed proteins (DEPs) from omics experiments are screened firstly, and KEGG and disease ontology (DO) databases can then be called online by R language platform with the screened DEGs or DEPs to identify enriched pathways and related diseases usually using a two-tailed Fisher’s exact test.…”
Section: Introductionmentioning
confidence: 99%